The impact of soil chloride concentration and salt type on the excretions of four recretohalophytes with different excretion mechanisms. Issue 11 (18th September 2020) - Litalien, Amélie A. S.; Rutter, Allison; Zeeb, Barbara A.
Abstract: Four natives Canadian recretohalophytic species: Atriplex canescens, Armeria maritima, Spartina pectinata, and Distichlis spicata were examined to determine their relative uptake and excretion of chloride in the context of phytoremediation. Adult plants were grown in soils contaminated with either sodium chloride or potassium chloride at various concentrations, then manually washed to collect the excreted salts. Atriplex canescens which has salt bladders, was found to have negligible excretions, suggesting that these structures release minimal amounts of salt onto the leaf's surface. Chloride excretions of S. pectinata and D. spicata increased with higher soil chloride concentrations. A. maritima showed minimal excretion until a threshold soil salinity was reached. This species shifted from a reliance on internal sequestration to secretion at higher soil salinity. The salt used in the media did not impact these trends, but D. spicata excreted significantly more chloride under sodium chloride conditions. While all four species studied were able to translocate significant amount of salt to their shoots, only S. pectinata, D. spicata, and A. maritima are suitable candidates for remediation by haloconduction. Among these, A. maritima showed the greatest potential and significantly reduced the soil chloride concentration by up to 60% in the highest concentration treatment (4 mg/g). HIGHLIGHTS: Armeria maritima, Spartina pectinata, and Distichlis spicata are suitable species for remediation via haloconduction. Armeria maritima had the highest total extraction capacity at high soil chloride. Spartina pectinata had the most consistent excretion capacity and is the most suitable for remediation of soils with lower soil chloride.